2020
DOI: 10.3389/fonc.2020.01560
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative CT Extent of Lung Damage in COVID-19 Pneumonia Is an Independent Risk Factor for Inpatient Mortality in a Population of Cancer Patients: A Prospective Study

Abstract: Background: CT lung extent has emerged as a potential risk factor of COVID-19 pneumonia severity with mainly semiquantitative assessment, and outcome was not assessed in the specific oncology setting. The main goal was to evaluate the prognostic role of quantitative assessment of the extent of lung damage for early mortality of patients with COVID-19 pneumonia in cancer patients. Methods: We prospectively included consecutive cancer patients with recent onset of COVID-19 pneumonia assessed by chest CT between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Previous studies have reported that age is a risk factor for severe COVID-19. ( Cheung et al, 2005 ; Ramtohul et al, 2020 ; Nawar et al, 2020 ) Fei Zhou et al analyzed 191 patients with severe COVID-19 requiring hospitalization. In this cohort, patients had a median age of 56.0 years.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that age is a risk factor for severe COVID-19. ( Cheung et al, 2005 ; Ramtohul et al, 2020 ; Nawar et al, 2020 ) Fei Zhou et al analyzed 191 patients with severe COVID-19 requiring hospitalization. In this cohort, patients had a median age of 56.0 years.…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen papers developed models for the prognosis of patients with COVID-19 51,[63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] , fifteen using CT and four using CXR. These models were developed for predicting severity of outcomes including: death or need for ventilation 72,78,79 , a need for intensive care unit (ICU) admission 63,73,[77][78][79] , progression to acute respiratory distress syndrome 80 , the length of hospital stay 51,74 , likelihood of conversion to severe disease 64,65,75 and the extent of lung infection 76 . Most papers used models based on a multivariable Cox proportional hazards model 51,72,78,79 , logistic regression 65,[73][74][75]80 , linear regression 75,76 , random forest 74,7...…”
Section: Diagnostic Models For Covid-19 Diagnosis Models Using Cxrsmentioning
confidence: 99%
“…These models were developed for predicting severity of outcomes including: death or need for ventilation 72,78,79 , a need for intensive care unit (ICU) admission 63,73,[77][78][79] , progression to acute respiratory distress syndrome 80 , the length of hospital stay 51,74 , likelihood of conversion to severe disease 64,65,75 and the extent of lung infection 76 . Most papers used models based on a multivariable Cox proportional hazards model 51,72,78,79 , logistic regression 65,[73][74][75]80 , linear regression 75,76 , random forest 74,77 or compare a huge variety of machine learning models such as tree-based methods, support vector machines, neural networks and nearestneighbour clustering 63,64 .…”
Section: Diagnostic Models For Covid-19 Diagnosis Models Using Cxrsmentioning
confidence: 99%
See 2 more Smart Citations